Pheno-morphological traits of diverse Brassica juncea (L.) genotypes determining variability in Lipaphis erysimi (Kaltenbach) population build-up (Journal of Oilseed Brassica, 2026)
Role of Brassica juncea pheno-morphological variation in imparting resistance to Lipaphis erysimi was studied. There was significant variation for most phenotypic and yield attributing traits, and aphid resistance indices on the test genotypes, across seasons, and for genotype × season interactions. Genotype RBJ 49 with longer siliquae, greater number of siliquae and seeds per siliqua was found with moderate aphid resistance. Taller genotypes PDZ 6 and RBJ 11 with small siliquae although took longer time to flower and mature, aphid resistance indices were lower than on other genotypes. Genotype IC 355399 having bunchy inflorescence, dark yellow flowers and higher siliquae, harboured greater aphids, while GP 454 and RP 11-2-1-3-1 having cream colour petals displayed opposite reaction towards aphids. In spite of significant variability in test genotypes for seedling colour, petal colour and siliquae orientation, their regression coefficients were nonsignificant with number of aphids and aphid resistance indices. However, path coefficient analysis revealed that number of aphids, aphid population and damage indices, point to first branch and siliqua, seeds per siliqua, total siliquae and siliquae length have significant association with aphid resistance index, indicating that these traits directly or indirectly contribute to differential reaction against L. erysimi in B. juncea.